Memory Acts: A Theory for the Study of Collective Memory in Everyday Life - de Saint-Laurent, Constance (My University, 2018)
History abounds in everyday life: It is in the discourse of the politician who makes a patriotic use of World War II, in the epic movie of medieval inspiration, in the latest museum opening in town, or in the magnet on your fridge that makes a humoristic use of advertisement posters from the 1950s. What tools can help us understand how history is used in these contexts, and with what purposes? And, more importantly perhaps, how to understand the effects these uses have on us? To answer these questions, this article proposes a framework to study the uses of collective memory in everyday life. After a short review of the history of collective memory, the concept of memory act is outlined, based on three theoretical traditions: James's pragmatism, Austin's speech acts, and Mead's social acts. They are used to argue that everyday uses of collective memory are better understood as intersubjective and discursive acts that are part of larger activities. Finally, some of the consequences of this theory are discussed.
Keywords: Karst aquifers; Global response; Recession coefficient; Conduit network geometry; Hydraulic parameters; Groundwater flow models